Meningkatkan Berfikir Kritis Menggunakan Kombinasi Model PBL, PP, TPS di SDN Kabupaten Kotabaru - Dwi Kartika Rahmawati Edi; Chresty Anggreani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study was conducted to improve students’ critical thinking skills through the implementation of a combined learning model consisting of Problem-Based Learning (PBL), Project-Based Learning (PP), and Think–Pair–Share (TPS) at SDN Sidomulyo, Kotabaru Regency. The participants of this study were 14 elementary school students. The research employed a Classroom Action Research (CAR) design, which was carried out over three instructional meetings. Each cycle consisted of planning, implementation, observation, and reflection stages. Data were collected through observation sheets, assessments of student learning activities, and evaluation of learning outcomes. The results of the study showed a consistent improvement in teacher performance, student learning activities, and learning outcomes across the three meetings. Teacher activity scores increased from 60% in the first meeting to 78% in the second meeting and further improved to 85% in the third meeting. Similarly, student learning activity levels rose from 57% in the first meeting to 68% in the second meeting and reached 81% in the third meeting. In terms of learning outcomes, students demonstrated significant progress, with achievement levels increasing from 60% in the first meeting to 90% in the third meeting. These findings indicate that the integration of PBL, PP, and TPS models effectively promotes active learning, collaboration, and critical thinking skills among elementary school students. The combination of these instructional models encourages students to engage in problem-solving, discussion, and project-based activities, which positively impacts their learning performance. Therefore, it can be concluded that the combined application of PBL, PP, and TPS is effective in enhancing students’ critical thinking skills, learning activities, and overall learning outcomes in the classroom.